The Cambridge companion to the body in literature - Hillman, David; Hillman, David (David A.); Maude, Ulrika (New York, NY : Cambridge University Press, 2015)
"This Companion offers the first systematic analysis of the representation of the body in literature. It historicizes embodiment by charting our evolving understanding of the body from the Middle Ages to the present day, and addresses such questions as sensory perception, technology, language and affect; maternal bodies, disability and the representation of ageing; eating and obesity, pain, death and dying; and racialized and posthuman bodies. This Companion also considers science and its construction of the body through disciplines such as obstetrics, sexology and neurology. Leading scholars in the field devote special attention to poetry, prose, drama and film, and chart a variety of theoretical understandings of the body"--
Machine generated contents note: 1. Medieval somatics Bill Burgwinkle; 2. Disability Jonathan Hsy; 3. Staging early modern embodiment David Hillman; 4. Eating, obesity and literature Maud Ellmann; 5. The body and language Andrew Bennett; 6. The maternal body Clare Hanson; 7. Literary sexualities Heike Bauer; 8. The body, pain, and violence Peter Fifield; 9. The ageing body Elizabeth Barry; 10. Representing dead and dying bodies Sander Gilman; 11. The racialized body David Marriott; 12. Literature, technology and the senses Steven Connor; 13. Literature and neurology Ulrika Maude; 14. Psychoanalytic bodies Josh Cohen; 15. The body and affect Jean-Michael Rabate; 16. Posthuman bodies Paul Sheehan.
/ -
Includes bibliographical references and index.
Keywords: Human body in literature; Human body in motion pictures; Human body -- Social aspects; Mind and body; Human body -- History